Practice of Audio-Visual Learning Media to Grow the Motivation of MI Kenongomulyo Students' Learning - Nur Aprianto, Wahyu; Irvan Sir; Amir, Atmam (Education and Talent Development Center Indonesia (ETDC Indonesia), 2022)
The development of science and technology today has a very significant impact on many aspects of life, including education. The use of IT media will attract more students' attention in a lesson. This study aims to see whether or not there is an effect of applying audio-visual learning media to foster learning motivation. This research uses an experimental method. The analysis of the data used is to perform a prerequisite test of normality test analysis using the Shapiro-Wilk test. The results of data analysis show that the t count is 7.725 and the t table is 2.110. The conclusion is that there is an effect on the application of audio-visual learning media to foster learning motivation for the fifth-grade students of MI Kenongomulyo PJOK.